MiR-429 Determines Poor Outcome and Inhibits Pancreatic Ductal Adenocarcinoma Growth by Targeting TBK1 - Bin Song (Cellular Physiology and Biochemistry, 2015)
Background: Pancreatic ductal adenocarcinoma (PDAC) ranks fourth on the list of cancer-related causes of death and its prognosis has not improved significantly over the past decades. Deregulation or dysfunction of miRNAs contribute to cancer development. Previous data indicates that miR-429 is involved in the pathogenesis of PDAC. However, the role of miR-429 in PDAC remained unknown. Methods: MiR-429 levels in sample tissues of 78 patients and in PANC1 and SW1990 cell lines were quantified by real-time PCR. MiR-429 expression was modulated using specific pre- and anti-miRNAs and cell growth was assayed by MTT analysis. Bioinformatics prediction of the miR-429 putative target genes was performed and luciferase assays confirmed TBK1 as a direct target gene. TBK1 levels in PDAC tissues were analyzed by immunohistochemistry. Results: MiR-429 was remarkably decreased in PDAC tissues and cell lines. Lower miR-429 expression in PDAC tissues significantly correlated with shorter survival of PDAC patients. Overexpression of miR-429 inhibited PDAC cell lines growth in vitro and vice versa. TBK1 was found to be the direct target gene of miR-429. Higher TBK1 protein level in PDAC tissues correlated with shorter survival of PDAC patients. Overexpression of TBK1 partly restored cell proliferation. Conclusions: Low level of miR-429 and high level of TBK1 in PDAC promoted PDAC cells growth which might be related to the low survival rate of PDAC patients. MiR-429 play its role in PDAC by targeting TBK1.